2007
DOI: 10.1128/jvi.02336-05
|View full text |Cite|
|
Sign up to set email alerts
|

Role for Nonstructural Protein 1 of Severe Acute Respiratory Syndrome Coronavirus in Chemokine Dysregulation

Abstract: Severe acute respiratory syndrome (SARS) is an emerging infectious disease caused by a novel coronavirus. Since its associated morbidity and mortality have been postulated to be due to immune dysregulation, we investigated which of the viral proteins is responsible for chemokine overexpression. To delineate the viral and cellular factor interactions, the role of four SARS coronavirus proteins, including nonstructural protein 1 (nsp-1), nsp-5, envelope, and membrane, were examined in terms of cytokine induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 25 publications
3
58
1
Order By: Relevance
“…SARS-CoV up-regulates pro-inflammatory cytokines like IFN-γ, IL-18, TGF-β1, TNF-α, IL-6, IP-10, MCP-1, MIG, and IL-8 (Huang et al, 2005;He et al, 2006), in which recruits immune responder cells into the lungs, triggers acute respiratory distress syndrome (ARDS), and even causes lung fibrosis in the late phase (Huang et al, 2005;He et al, 2006). Among SARS-CoV proteins, the nucleocapsid induces a Smad3dependent induction of TGF-β1 expression (Zhao et al, 2008); spike protein stimulates the IL-8 up-regulation in lung cells (Chang et al, 2004); NSP1 provokes the expression of CCL5, CXVL10, and CCL3 (Law et al, 2007); PLpro elavates the production of TGF-β1 and pro-fibrotic markers via ubiquitin proteasome, p38 MAPK, and ERK1/2-mediated signaling (Li et al, 2012). Recently, SARS-CoV PLpro notably initiates ROS/p38 MAPK/STAT3 pathway to activate Egr-1 dependent expression of TSP-1, TGF-β1 and vimentin in vitro and in vivo (Li et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV up-regulates pro-inflammatory cytokines like IFN-γ, IL-18, TGF-β1, TNF-α, IL-6, IP-10, MCP-1, MIG, and IL-8 (Huang et al, 2005;He et al, 2006), in which recruits immune responder cells into the lungs, triggers acute respiratory distress syndrome (ARDS), and even causes lung fibrosis in the late phase (Huang et al, 2005;He et al, 2006). Among SARS-CoV proteins, the nucleocapsid induces a Smad3dependent induction of TGF-β1 expression (Zhao et al, 2008); spike protein stimulates the IL-8 up-regulation in lung cells (Chang et al, 2004); NSP1 provokes the expression of CCL5, CXVL10, and CCL3 (Law et al, 2007); PLpro elavates the production of TGF-β1 and pro-fibrotic markers via ubiquitin proteasome, p38 MAPK, and ERK1/2-mediated signaling (Li et al, 2012). Recently, SARS-CoV PLpro notably initiates ROS/p38 MAPK/STAT3 pathway to activate Egr-1 dependent expression of TSP-1, TGF-β1 and vimentin in vitro and in vivo (Li et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…nsp1 and nsp2 are rather variable in sequence, and possibly subgroup-specific replicase subunits Ziebuhr et al, 2001). SARS-CoV nsp1 (20 kDa) was implicated in suppression of cellular gene expression by promoting host cell mRNA degradation (Kamitani et al, 2006) and in chemokine dysregulation (Law et al, 2007). SARS-CoV nsp2 (70 kDa) is dispensable for replication in cell culture, but its deletion attenuates viral replication (Graham et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that spike protein induces innate immune response through the activation of the nuclear factor-kappaB (NF-kB) pathway [75]. In addition, Law et al found that SARS-CoV NSP1 induces CCL5, CXVL10, and CCL3 mRNA expression via the activation of NF-kB [76]. The 3a DNA vaccine is reported to stimulate IFN-g production mainly by stimulating the production of CD8þ T cells, and IL-2 mainly by stimulating the production of CD4þ T cells [77].…”
mentioning
confidence: 99%